PROFESSIONAL BEHAVIOR BASED ON THE DEVELOPMENT OF EMPLOYEES - Sudarma, Ketut (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2014)
The objective of the study was to analyze the impact of work discipline management, career management and profession ethics management toward Unnes staffâs behavior. The samples were taken by proportional random sampling. The variables of the research were work discipline management, career management, profession ethics management and professional behavior. The data were analyzed by multiple regression analysis. The result of this study showed that discipline work management, career management and profession ethics management gave positive influence toward staffâs professional behavior. Furthermore, the result of percentage descriptive analysis showed that the average of work discipline management, career management, profession ethics management and professional behavior were on enough category.Â Tujuan penelitian ini adalah menganalisis dampak pembinaan disiplin kerja, pembinaan karir dan pembinaan etika profesi terhadap perilaku profesional tenaga kependidikan Sampel 50 orang tenaga kependidikan Unnes. Teknik pengambilan sampel menggunakan proporsional random sampling. Variabel penelitian adalah pembinaan disiplin kerja, pembinaan karir, pembinaan etika profesi dan perilaku profesional. Metode pengumpulan data menggunakan kuesioner. Analisis data menggunakan analisis regresi berganda. Hasil penelitian menunjukkan pembinaan disiplin kerja, pembinaan karir, pembinaan etika profesi berdampak positif terhadap perilaku profesional tenaga kependidikan Sedangkan dari hasil analisis deskriptif persentase tampak bahwa rata-rata pembinaan disiplin kerja, pembinaan karir, pembinaan etika profesi dan perilaku profesional termasuk kategori cukup.